Barriers and enablers in the implementation and sustainability of toothbrushing programs in early childhood settings and primary schools: a systematic review - Navira Chandio; Sowbhagya Micheal; Santosh Kumar Tadakmadla; Woosung Sohn; Susan Cartwright; Rhiannon White; Prathyusha Sanagavarapu; Jinal Shashin Parmar; Amit Arora (BMC, 2022)
Abstract Background Untreated dental caries negatively impacts a child's quality of life including overall health and wellbeing, growth and development, social interaction ability, and school attendance. School-based toothbrushing programs have been recognised as an effective intervention to reduce the burden of dental caries. However, limited information is available to understand the real-world enablers and challenges in the implementation and sustainability of toothbrushing programs. This review aims to understand the barriers and enablers in the implementation and sustainability of toothbrushing programs in early childhood settings and primary schools. Methods Five electronic databases [i.e., CINAHL (EBSCO), Medline (EBSCO), EMBASE (Ovid), Web of Science, and PsycINFO] and backward citation chasing were performed. The last updated databases searches were conducted in May 2022. Studies reporting on barriers and enablers in the implementation and sustainability of toothbrushing programs in early childhood settings or primary schools were included in the review. The methodological quality of included studies was assessed by using Joanna Briggs Institute [JBI] and mixed methods appraisal tool [MMAT] critical appraisal tools and results were reported in accordance with PRISMA guidelines. Results A total of six studies met the eligibility criteria and were included in the review. Toothbrushing programs in early childhood settings and primary schools were mostly implemented under the supervision of staff and teachers. A positive attitude of the staff, the flexibility of toothbrushing sessions, involvement of community volunteers and parents were a few of the identified enablers. However, the timing of the communication of the program, inadequate transfer of information among staff, frequent staffing turnover, lack of parental support, and staff feeling overburdened while acting as pseudo parents were frequently reported as barriers. Conclusion The results of this systematic review identify key enablers and barriers for toothbrushing programs in early childhood settings and primary schools which need to be considered for developing oral health promotion initiatives.